Agitación en el campo. Nueve ideas para la investigación sobre Comunicación Política en España - Martínez Nicolás, Manuel (Política y Sociedad, 2008)
Since near a decade ago, the field of the Political Communication is one of the most dynamical in Spanish communication research. Aset of factors related to the socio-political, institutional and scientific contexts explain the ferment in this field of research in Spain. This situation could be strengthened on condition that the scientific community begins to think over and debate on its work. With this aim, we propose here nine thoughts on Political Communication research, taken as a starting point the concepts of public sphere, interaction, political processes, political infotainment, new technologies, contextualism, comparative research, interdisciplinarity and scientific method